Study on tea leaves extract as green corrosion inhibitor of mild steel in hydrochloric acid solution - Hamdan, A B; Suryanto, Suryanto; I. Haider, Farag (Institute of Physics, 2017)
Corrosion inhibitor from extraction of plant has been considered as the most preferable and most chosen technique to prevent corrosion of metal in acidic medium because of the environmental friendly factor. In this study, black tea leaves extraction was tested as corrosion inhibitor for mild steel in 0.1M of hydrochloric acid (HCl) with the absence and presence of corrosion inhibitor. The efficiency and effectiveness of black tea as corrosion inhibitor was tested by using corrosion weight loss measurement experiment was carried out with varies parameters which with different concentration of black tea extract solution. The extraction of black tea solution was done by using aqueous solvent method. The FT-IR result shows that black tea extract containing compounds such as catechin, caffeine and tannins that act as anti-corrosive reagents and responsible to enhance the effectiveness of black tea extract as corrosion inhibitor by forming the hydrophobic thin film through absorption process. As a result of weight loss measurement, it shows that loss in weight of mild steel reduces as the concentration of inhibitor increases. The surface analysis was done on the mild steel samples by using SEM.